Nanomaterials Preparation by Thermolysis of Metal Chelates - Uflyand, Igor E.; Dzhardimalieva, Gulzhian I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book focuses on the thermal transformations of various types of metal chelates, e.g. low molecular weight and polymeric metal chelates, coordination polymers and metal-organic frameworks. It analyzes the major advances and the problems in the preparation of metal oxide materials, mixed-oxide nanocomposites, carbon materials and polymer derived non-oxide nanocomposites by the thermolysis of different metal chelates. It also highlights the influence of the spatial and electronic structure of metal chelates on the mechanism and kinetics of their thermal transformations, and discusses important issues like conjugate thermolysis and computer modelling of the thermolysis process. This book is useful for researchers experienced in thermolysis as well as for young scientists interested in this area of science.
Preface -- General Introduction -- General Characterization of Thermolysis Methods of Metal Compounds -- Thermolysis of Low Molecular Weight Metal Chelates -- Thermolysis of Polymeric Metal Chelates -- The Conjugate Thermolysis - Thermal Polymerization of Metal Chelate Monomers and Thermolysis of Polymers formed in situ -- Thermolysis of Metal Chelates in Polymer Matrices -- Application of Nanomaterials Prepared by Thermolysis of Metal Chelates -- Conclusions and Future Prospects -- Index.
Keywords: Nanochemistry; Polymers; Nanotechnology; Organometallic chemistry .; Metals; Nanochemistry; Polymers; Nanotechnology; Organometallic Chemistry; Metals and Alloys